The mystery of the Chinese junk. - Dixon, Franklin W. (New York, Grosset & Dunlap, 1960)
The Hardys purchase a Chinese junk to use as a ferry service, in order to make some money over the summer. It soon becomes apparent that others are very interested in the ship.
Keywords: Chinese -- Action